NF-κB-dependent repression of Sox18 transcription factor requires the epigenetic regulators histone deacetylases 1 and 2 in acute lung injury - Zemskov, Evgeny A.; Gross, Christine M.; Aggarwal, Saurabh; Zemskova, Marina A.; Wu, Xiaomin; Gu, Chenxin; Wang, Ting; Tang, Haiyang; Black, Stephen M. (Frontiers in Physiology, 2022)
In acute lung injury (ALI), the NF-kB-mediated downregulation of Sox18 gene expression leads to the disruption of the pulmonary endothelial barrier. Previous studies have suggested that the action of NF-kB as a transcriptional repressor also requires the action of class I histone deacetylases (HDACs). Thus, the purpose of this study was to investigate and further delineate the mechanism of Sox18 repression during lipopolysaccharide (LPS) induced ALI. Using selective inhibitors and specific siRNA-driven depletion of HDACs 1-3 in human lung microvascular endothelial cells (HLMVEC) we were able to demonstrate a critical role for HDACs 1 and 2 in the LPS-mediated repression of Sox18 gene expression and the loss of endothelial monolayer integrity. Moreover, our data demonstrate that HDAC1 associates with a transcription-repressive complex within the NF-kB-binding site of Sox18 promoter. Further, we were able to show that the selective inhibitor of HDAC1, tacedinaline, significantly reduced the endothelial permeability and injury associated with LPS challenge in the mouse lung. Taken together, our data demonstrate, for the first time, that transcription repressors HDACs 1 and 2 are involved in pathological mechanism of ALI and can be considered as therapeutic targets.